Pre-Entry Knowledge, Learning, and the Survival of New Firms - Dencker, John C.; Gruber, Marc; Shah, Sonali K. (Organization Science, 2009)
New firms are endowed with knowledge and experience at birth through the human capital of their founder(s). Existing empirical research suggests that this pre-entry knowledge and experience will influence the firm's chances of survival; however, the mechanisms underlying this relationship have yet to be investigated. We seek to better understand and unpack this relationship. Specifically, we study the extent to which a founder's pre-entry knowledge of the business activity and pre-entry management experience influence the effectiveness of two subsequent learning activities—namely, early-stage business planning and product-line change. Our findings suggest that pre-entry knowledge and management experience increase firm survival through moderating the effects of these subsequent learning activities. We also find that learning activities are not always beneficial; in our sample, early-stage business planning is associated with decreased firm survival, and product line change is associated with increased firm survival. We examine these patterns using survey data collected from 436 individuals in the Munich region who founded their own firms as an alternative to continued unemployment. Our results have theoretical implications for the entrepreneurship, evolutionary economics, and organizational learning literatures.